Enhanced single cell oil production by mixed culture of Chlorella pyrenoidosa and Rhodotorula glutinis using cassava bagasse hydrolysate as carbon source - Liu, Lu; Chen, Junhui; Lim, Phaik Eem; Wei, Dong (Elsevier, 2018)
The single cell oil (SCO) production by the mono and mixed culture of microalgae Chlorella pyrenoidosa and red yeast Rhodotorula glutinis was investigated using non-detoxified cassava bagasse hydrolysate (CBH) as carbon source. The results suggested that the two strains were able to tolerate and even degrade some byproducts presented in the CBH, and the mixed culture approach enhanced the degradation of certain byproducts. Biomass (20.37 ± 0.38 g/L) and lipid yield (10.42 ± 1.21 g/L) of the mixed culture achieved in the batch culture were significantly higher than that of the mono-cultures (p < 0.05). The fed-batch culture further raised the biomass and lipid yield to 31.45 ± 4.93 g/L and 18.47 ± 3.25 g/L, respectively. The lipids mainly composed of oleic acid and palmitic acid, suggesting the potential applications such as biofuel feedstock, cosmetics, food additives and lubricant. This study provided new insights for the integration of the economical SCO production with agro-industrial waste disposal.